The Usage Effectivity of Project-Based Interactive E-Module in Improving Students’ Achievement - Komang Redy Winatha; Myra Mentari Abubakar (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
One of the changes done by the government in the field of education is changing Curriculum 2006 to be Curriculum 2013. This change impacts on the change of learning paradigm, which at the beginning it was teacher-centered learning changes to be students centered learning. Therefore, the learning strategy used by teachers should be addressed to facilitate competence achievement that in the end, it will improve students' achievement. This study was aimed to identify the effectivity of project-based interactive e-module media towards students' achievement in the subject of digital simulation. This study was categorized into pre-experimental quantitative research with one group pretest-posttest design. The data analysis method used was a paired sample t-test. The results showed the significance value obtained was 0.000 which means higher than α. This means that there is an average score difference of students' achievement between before and after using the project based interactive e-module. The post-test average score is 82.65 which is higher than the average pre-test score of 43.40. It can be concluded that digital simulation learning by using the project based interactive e-module can improve the students’ achievement.